Legal analysis of parking service providers' liability for consumer losses - Ayang Fristia Maulana; Asnawi Asnawi; Yashifa Nazwa Ramadhanty; Risa Bintang Saecar; Adrikni Illahiya (Journal of Law Science, 2024)
The increasing use of private vehicles in urban areas has led to the growth of parking services, but often gives rise to legal conflicts when vehicles are lost or damaged. This study aims to review the form of legal responsibility of parking service providers towards consumers, especially when exoneration clauses are used as a basis for exemption from responsibility. With a normative juridical approach and a literature study of Law Number 8 of 1999 concerning Consumer Protection, this study demonstrates that the responsibility of service providers is absolute (strict liability), whereby they are still obliged to provide compensation even if they are not proven to be directly negligent. The results of the study also reveal that exoneration clauses included unilaterally in parking tickets are contrary to the principle of contractual justice and are declared invalid under law. Therefore, it is important to strengthen regulations and educate consumers about their rights to obtain protection against losses. These findings are expected to contribute to the formulation of a  fairer policy in the parking service sector.